Purified Vitexin Compound 1 Serves as a Promising Antineoplastic Agent in Ovarian Cancer - Ma, Kewen; Wang, Kuansong; Zhou, Yingjun; Liu, Nian; Guo, Wei; Qi, Jialin; Hu, Zhenmin; Su, Shitong; Tang, Ping; Zhou, Xunjian (Frontiers in Oncology, 2021)
Ovarian cancer is a common gynecologic aggressive neoplasm. The mortality of ovarian cancer is top among gynecologic malignancies due to the insidious onset, atypical early symptoms, and chemoresistance. Therefore, it is urgent to seek another promising treatment for ovarian cancer. Purified vitexin compound 1 (VB1) is a kind of neolignan from the seed of traditional Chinese herb vitex negundo that possessed diverse pharmacological effects. VB1 can exhibit anti-neoplastic activities against various cancers. However, the role of VB1 in ovarian cancer treatment has not been elaborated, and the mechanism is unknown. The aim of this study was to investigate the therapeutic effects of VB1 in ovarian cancer cells both in vitro and in vivo, along with the molecular mechanism of action. In vitro, VB-1 can effectively suppress the proliferation, induce apoptosis, and block cell cycle at G2/M phase with a concentration dependent manner in ovarian cancer cells. Western blot assay showed that VB1 induce apoptosis via upregulating expression of cleaved-caspase3 and block cell cycle at G2/M phase through upregulating expression of P21. Meanwhile, VB1 can effectively inhibit tumor growth in xenograft mouse model. Our research indicated that VB1 can significantly exert its anti-neoplastic effects and may represent a new class of agents in ovarian cancer therapy.